REHABILITAS JALAN DI M.ISA PALEMBANG - Simangunsong, Yoel Febrian; Mulyati, Ely (Ensiklopedia Research and Community Service Review, 2025)
Roads are land transportation infrastructure that includes all parts of the road, including complementary structures and equipment, intended for traffic, located on the ground surface, above the ground surface, underground, and on or under water surfaces, excluding railroads, tramways, and cableways. The function of highways as transportation infrastructure in economic activities is to promote economic equity by serving as a connecting network. Rehabilitation is the solution to damages caused by excessive vehicle loads and frequent changes in weather and climate. Road rehabilitation involves resurfacing, restoration, and rehabilitation of existing pavement layers to extend their service life, improve performance, and enhance the durability of pavement structures. To restore the service conditions of roads, regular maintenance is essential. One type of road maintenance is road improvement, which may include upgrading pavement structures or widening roads to increase their capacity. The implementation of road rehabilitation on Jalan M. Isa is a critical effort to improve vital urban transportation infrastructure, given the high levels of damage in several sections caused by aging, traffic loads, and weather conditions. The government builds transportation infrastructure according to the needs of each region to foster regional development. This study examines whether the road rehabilitation methods applied on Jalan M. Isa comply with existing technical standards and align with the 2023 General Specifications of Bina Marga. The type of asphalt used in the rehabilitation of Jalan M. Isa in Palembang City is AC-WC (Asphalt Concrete Wearing Course), with damage assessments conducted using the PCI (Pavement Condition Index) method.Keywords: Road rehabilitation, M. Isa Palembang, Traffic density, Transportation infrastructure,PCI